Truncating mutations of TP53AIP1 gene predispose to cutaneous melanoma. Issue 6 (21st February 2018) - Benfodda, Meriem; Gazal, Steven; Descamps, Vincent; Basset‐Seguin, Nicole; Deschamps, Lydia; Thomas, Luc; Lebbe, Celeste; Saiag, Philippe; Zanetti, Roberto; Sacchetto, Lidia; Chiorino, Giovanna; Scatolini, Maria; et al.
Abstract: Genetic predisposition to cutaneous malignant melanoma (CMM) involves highly penetrant predisposing genes and low and intermediate penetrant predisposing alleles. However, the missing heritability in (CMM) is still high. For such and in order to identify new genetic factors for CMM, we conducted an exome sequencing study in high‐risk CMM patients. Two rounds of exome sequencing were successively performed in 33 and 27 high‐risk patients. We focused on genes carrying rare nonsense, frameshift, and splice variants (allelic frequency <1%) that were present in both series of exomes. An extension study was then conducted in a large cohort (1 079 CMM patients and 1 230 Caucasian ethnically matched healthy controls), and the inactivating variants frequency was compared between groups using two‐sided Fisher exact test. Two TP53AIP1 truncating mutations were identified in four patients: a frameshift c.63_64insG, p.Q22Afs*81 in two patients from the same family and in the proband of a second family; and a nonsense mutation c.95 C > A, p.Ser32Stop in a patient with multiple CMMs. In all patients, TP53AIP1 truncating variants were strongly associated with CMM risk (two‐sided Fisher exact test = 0.004, OR = 3.3[1.3‐8.5]). Additionally, we showed that TP53AIP1 mRNA was strongly down‐regulated throughout different phases of melanoma progression. TP53AIP1 gene is a TP53 target which plays a key role by inducting apoptosis in response to UV‐induced DNA damage. Constitutional mutations of TP53AIP1 had previously been involved in susceptibility to prostate cancer. Our results show that constitutional truncating TP53AIP1 mutations predispose to CMM in the French population. Replication studies in other populations should be performed.